2020
DOI: 10.7705/biomedica.5516
|View full text |Cite
|
Sign up to set email alerts
|

Coinfección por SARS-CoV-2 y rinovirus-enterovirus en una paciente adulta joven críticamente enferma en Colombia

Abstract: La actual pandemia por SARS-CoV-2 ha ocasionado un enorme problema de salud pública mundial. Se reporta el caso de una paciente adulta joven con SARS-CoV-2 confirmado por laboratorio. Se describe la identificación del virus y el curso clínico, el diagnóstico y el tratamiento de la infección. La paciente tuvo un rápido deterioro clínico a partir de síntomas iniciales leves que progresaron a una neumonía multilobar que requirió su hospitalización en la unidad de cuidados intensivos.Se destaca la importancia de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In Brazil, it was documented that one patient presented Lautropia , Prevotella, and Haemophilus [ 17 ]. Finally, Orozco-Hernández et al reported a case of coinfection with rhinovirus and enterovirus in Colombia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it was documented that one patient presented Lautropia , Prevotella, and Haemophilus [ 17 ]. Finally, Orozco-Hernández et al reported a case of coinfection with rhinovirus and enterovirus in Colombia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Orozco-Hernández et al 7 reported it in an obese young adult with coinfection by SARS-CoV-2 and rhinovirus/enterovirus, who developed severe multilobar pneumonia requiring support in intensive care unit. 7 Based on these reports, the use of the respiratory panel (RP) for the multiple pathogens identification (RP-FilmArray), as well as the performance of cultures for specific pathogens is recommended especially in severe cases or in scenarios where a positive result would change disease management (eg, for the identification of bacterial resistance or neuraminidase inhibitors for influenza in appropriate patients) to prevent disease progression or death. [2][3][4]6 The identification of clinical and epidemiological risk factors of each patient that could suggest a coinfection by a virus, bacteria, and fungi, even three pathogens as Ou et al, 6 and Cuadrado-Payán et al 10 reported.…”
Section: Covid-19 Arrived In Latin America and The Caribbean On 25mentioning
confidence: 99%
“…There are in summary at least ten reports of different coinfecting organisms isolated simultaneously with SARS-CoV-2 ( Table 1). [1][2][3][4][5][6][7][8][9][10] Even more, recently, two brief reviews without meta-analysis found additional cases, 11,12 although not necessarily included in the current assessment of coinfections. In one of them, published on 2 May 2020, they found that 8% of patients with COVID-19 experienced a bacterial/fungal coinfection during hospital admission, based on 18 studies included.…”
Section: Covid-19 Arrived In Latin America and The Caribbean On 25mentioning
confidence: 99%
See 2 more Smart Citations